Complete Hydatidiform Mole in a Perimenopausal Woman: Clinical Case - Hernández-Albino, Maira Fernanda; Rodríguez-Villalobos, Paula Cecilia; González-Rodríguez, Patricia Alejandra; Villalobos Rodríguez, Alejandro Lenin; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
Background: Hydatidiform moles are divided into a complete mole and partial mole, the former originates from the fertilization of an enucleated ovum by two spermatozoa with independent genetic load and the predominant clinical manifestation is hemorrhage. The uterine size is usually larger than normal with subjective symptoms of pregnancy. The importance of this type of tumor is that it is a pre-malignant tumor that can develop into a trophoblastic neoplasm in such a way that in the complete mole it will transform into a neoplasm. Clinical case: A 43-year- old female attends for evaluation after suffering a fall from her support plane for 3 days with pelvic and hypogastric pain, colic type without transvaginal bleeding, reports pregnancy, unaware of her date of the last period, without prenatal control or previous USG. On physical examination: globular abdomen at the expense of a hypertrophic uterus of 16x12x10 cm, beta chorionic gonadotrophic hormone (HGC- ß) > 150,000.00 mIU/ml. Endovaginal and pelvic USG: uterus in anteversoflexion, central, enlarged due to the presence of a snowflakes ultrasound image. Diagnosis: data suggestive of hydatidiform mole. She has been admitted for an abdominal hysterectomy. Findings: enlarged uterus at the expense of a complete mole, adnexa without alterations. Discussion: Hydatidiform mole can occur in both reproductive and peri or postmenopausal. Conclusion: Our case was presented in an elderly patient with an incidental diagnosis by ultrasound and with the management established for this type of case in elderly people who have resolved their parity, which evolved satisfactorily under surveillance by the service.